Phytochemical Screening and Antioxidant Activity Test of Ethanol Extracts of Local Plants Typical of Central Sulawesi as Candidates for Traditional Pharmaceutical Preparations - Putri Armin; Evi Andriani; Cut Intan (Magenta Journal De Healthymedi, 2026)
This study aimed to evaluate the phytochemical composition and antioxidant activity of ethanol extracts obtained from selected medicinal plants originating from Central Sulawesi as potential candidates for traditional pharmaceutical preparations. An experimental laboratory approach was employed involving ethanol extraction, qualitative phytochemical screening, and antioxidant activity assessment using a radical scavenging assay. The results revealed the presence of multiple secondary metabolites, including flavonoids, tannins, alkaloids, saponins, and terpenoids. All investigated extracts demonstrated concentration-dependent antioxidant activity. Among the tested species, Moringa oleifera and Syzygium polyanthum exhibited the strongest antioxidant performance, with IC50 values of 45.2 ppm and 49.7 ppm, respectively. The findings indicate that medicinal plants from Central Sulawesi represent promising natural sources of antioxidant compounds and possess significant potential for the development of traditional pharmaceutical products. This study provides scientific evidence supporting the utilization of regional medicinal plant resources while contributing to future research and innovation in natural product-based healthcare development.